Implementación de un sistema web apoyado en pruebas unitarias para la administración de guiones y publicidad en la radio ciudad - Campos Curizaca, Julio David (2022)
This research objective was to develop a web system based on unit tests to offer a computer tool that allows automating the process of managing scripts, radio programs, and advertising, thus establishing control of the same techniques broadcast on Radio Ciudad 106.5 F.M. The Java programming language is using as an integrated development environment. Netbeans IDE 8.2 was worked on, Java Server Face technology was also used for web systems applied to the radio's Web system, and the Bootstrap interface design framework was used for the different styles for the web system of the radio will have. For the elaboration of the database for the project, it is implementing with PostgreSQL technology. Taking into account the life cycle of the software in V, accompanied by the SCRUM development methodology, the same that the execution of the requirements obtained from the radio producer was planned, in this way, with the help of the radio producer and All the people committed to the radio, together with the developer, proceed to build the system, resulting in a web system for the radio by the needs of the entity specified above. The implementation of the unit tests was carried out with JUnit and thus verified and validated the design of the different modules of the system, guaranteeing an acceptable percentage of the correct functioning of the other modules that are made up of the web system of the radio. In addition, with the use of unit tests, each user story of the project was executed, and as a result, a range of 80% - 100% execution was obtained. After having carried out a statistical study, it was shown that the time spent in each process using the system showed a significant difference concerning the procedures carried out manually, thus verifying the proposed hypothesis